Increased carrier volume improves preemergence control of rigid ryegrass (lolium rigidum) in zero-tillage seeding systems - Borger, C.; Riethmuller, G.; Ashworth, Michael; Minkey, D.; Hashem, A.; Powles, S. (2013)
PRE herbicides are less effective in the zero-tillage system because of increased residual crop stubble and reduced soil incorporation. However, since weeds are not physically controlled in the zero-tillage system, reliance on efficacy of PRE herbicides is increased. This research investigated the impact of carrier volume and droplet size on the performance of PRE herbicides (in wheat crops at four sites in 2010) to improve herbicide efficacy in conditions of high stubble biomass in zero-tillage systems. Increasing carrier volume from 30 to 150 L ha-1 increased spray coverage on water-sensitive paper from an average of 5 to 32%. Average control of rigid ryegrass by trifluralin (at Cunderdin and Merredin sites) and trifluralin or pyroxasulfone (at Wickepin and Esperance sites) improved from 53 to 78% with increasing carrier volume. Use of ASABE Medium droplet size improved spray coverage compared with ASABE Extremely Coarse droplet size, but did not affect herbicide performance. It is clear that increased carrier volume improves rigid ryegrass weed control for nonwater-soluble (trifluralin) and water-soluble (pyroxasulfone) PRE herbicides. Western Australian growers often use low carrier volumes to reduce time of spray application or because sufficient high-quality water is not available, but the advantages of improved weed control justifies the use of a high carrier volume in areas of high weed density.